WIF1 prevents Wnt5A mediated LIMK/CFL phosphorylation and adherens junction disruption in human vascular endothelial cells - Tom Skaria; Esther Bachli; Gabriele Schoedon (BMC, 2017)
Abstract Background Wnt5A is released by activated macrophages and elevated levels have been detected in sepsis patients with severe systemic inflammation. However, the signalling and functional effects of Wnt5A in the vascular endothelial cells (VEC) remained unclear. Recently, we showed that Wnt5A affects barrier function in human VEC through Ryk interaction. Wnt5A/Ryk signalling activates LIMK to inactivate the actin depolymerisation factor CFL by phosphorylation, promotes actin polymerisation and disrupts endothelial adherens junctions. Findings Here, we investigate the antagonistic effect of the Ryk specific secreted Wnt antagonist Wnt inhibitory factor (WIF)-1 on Wnt5A-mediated activation/inactivation of LIMK/CFL, and adherens junction disruption in human VEC. In human coronary artery endothelial cells (HCAEC), treatment with Wnt5A enhanced the phosphorylation of LIMK and CFL that was significantly prevented by WIF1. The presence of WIF1 suppressed Wnt5A-mediated disruption of β-catenin and VE-cadherin adherens junctions in HCAEC, thereby preventing barrier dysfunction caused by Wnt5A. Conclusion We conclude that WIF1 or molecules with similar properties could be potent tools for the prevention of vascular leakage due to Wnt5A-mediated actin cytoskeleton remodeling in diseases associated with systemic inflammation.